HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP PASIEN HIPERTENSI TENTANG PENGENDALIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SARITANI KABUPATEN BOALEMO - Tangahu, Ari Yudistira Perdana; Koesrini, Juliati (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2026)
Hypertension is a silent disease because people do not know they have it until they have their blood pressure checked. Hypertension is the biggest cause of stroke, both systolic and diastolic blood pressure. According to WHO data, around 972 million Indonesians aged 18 and over had hypertension in 2014. According to Boalemo Regency Health Profile Data for 2024, Saritani Community Health Center had 559 people with hypertension. Hypertension can be prevented and controlled by cultivating a healthy lifestyle. The public's lack of knowledge about hypertension and its preventive measures risks significantly increasing the prevalence of this disease. The high incidence of hypertension at Saritani Community Health Center is thought to be related to low self-control efforts even though sufferers may have been aware of their condition, or due to a lack of initial public awareness of their hypertension status. This condition underlies the urgency of conducting this research to evaluate the correlation between the level of knowledge and attitudes of patients in controlling hypertension in the working area of ​​the Saritani Health Center.